2019
DOI: 10.4193/rhinol/19.003
|View full text |Cite
|
Sign up to set email alerts
|

Nasal and salivary pepsin as a biomarker for gastroesophageal reflux in chronic rhinosinusitis

Abstract: Background: Gastro-esophageal reflux (GER) may be a contributing factor for some patients with chronic rhinosinusitis (CRS). The aim of the present study was to investigate if Peptest, an immunoassay for pepsin detection, could be used as a biomarker for GER in CRS. Methodology: Peptest was used to analyse 3 saliva and 3 nasal samples for pepsin A in 62 CRS-patients and 62 age and gender matched healthy controls. The results were correlated to 24-hour impedance pH-monitoring and symptom questionnaires. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 24 publications
3
4
0
Order By: Relevance
“…Our data showed a little difference in nasal and salivary pepsin between CRS-and controls and the insignificant difference in salivary and nasal pepsins' positivity, maybe in line with Katle et al [23] , though the results made due to the limited sensitivity and specificity of the Peptest.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Our data showed a little difference in nasal and salivary pepsin between CRS-and controls and the insignificant difference in salivary and nasal pepsins' positivity, maybe in line with Katle et al [23] , though the results made due to the limited sensitivity and specificity of the Peptest.…”
Section: Discussionsupporting
confidence: 90%
“…Also, pepsin in the nasal sample showed positivity only in the second and third samples in the CRS group than controls; they showed a statistically significant difference. This was parallel to Katle et al [23] , who stated that saliva or nasal secretions of patients with CRS did not have more pepsin when Peptest measured it in comparing their results to healthy controls. They postulated that CRS people with anomalous proximal reflux did not have more positive samples than people without reflux for Peptest.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Other studies have shown that proton pump inhibitor therapy improves reflux symptoms in CRS patients in 79-88% of cases (Beule, 2015). A recent study from Sweden showed that there was a less significant amount of pepsin difference in CRS patients (67.5%) compared to ordinary people (65.4%) through the detection of pepsin in saliva (p=1.00) (Katle et al, 2019). Based on these previous studies, this study was conducted to explain the correlation between CRS and LPR based on nasal pepsin examination.…”
Section: Introductionmentioning
confidence: 95%